(untitled) (Journal of Medical Device Technology, 2024)
Nowadays, there is an increasing effort to shift from using two-dimensional culture (2D) to three-dimensional culture (3D). This shift is led by the tissue engineering research study that needs to use the 3D culture system to form tissue graft. Agarose hydrogel has been widely used to provide a solid 3D environment for the cells due to its ability to support the cells and to mimic the extracellular matrix (ECM). In this study, 3D culture system was used to evaluate the agarose biodegradability and cell viability of BRIN-BD11 insulin-producing cells in culture. Results revealed the degradation rate of agarose was relatively slow for all concentrations. This could be due to the mechanical stiffness of agarose crosslinkers which gives support for the cells to grow and proliferate. MTT assay showed that cells viability decreased at higher agarose concentration (3%) and low seeding density (5×10⁴ cell/mL), could be due to the smaller pore size which limits the space for the cells to grow. Meanwhile, 1% agarose concentration enhanced cell viability the best (≈50%). Higher seeding densities, 1×10⁶ cell/mL was found to be more suitable for seeding on agarose at low concentration, could be due to the large pore size which allows movement of nutrients and accommodates large number of metabolizing cells. In conclusion, this study demonstrated that agarose hydrogel is a suitable and compatible material for 3D culture of D11 cells. Precisely, by altering the agarose concentration and the seeding density, cell proliferation in agarose can be controlled.